ÉTICA EN PUBLICIDAD ONLINE - Araceli Castelló Martínez (Fonseca, Journal of Communication, 2023)
Internet consolidation as an advertising medium requires a review of the legal and ethical principles applicable to advertising initiatives in the digital world, also taking into account the peculiarities of new digital platforms, such as the Social Media